IFPRI’s Support to CAADP in 2016–2017: Strengthening capacities for evidence-based policy planning and implementation in Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Since 2006, the International Food Policy Research Institute (IFPRI) has provided policy research and capacity strengthening support to guide the planning and implementation of the Comprehensive Africa Agriculture Development Programme (CAADP). Endorsed in 2003 by African heads of state and government, CAADP is a continentwide framework for accelerating growth and progress toward poverty reduction and food and nutrition security through an agriculture-led growth strategy.